Alimentação e nutrição escolar indígena: uma proposta de sequência didática - ARAÚJO, Talles Vinícius Machado de (2023)
The advancement of technologies and contact with urban centers influence the way of eating habits of indigenous communities, affecting their quality of life and health. In this context, an approach to indigenous school feeding is important to enhance traditional food culture and cuisine in order to rescue fishing, hunting and promote traditional agriculture, which is a vital part of the productive system. The general objective of this study is to propose a didactic sequence of the 8th year of Elementary School on the theme of indigenous school food and nutrition for the Juruna community of Vitória do Xingu/Pará. The sequence consists of six stages that address: a) diagnosis; b) application of knowledge; c) problematization; d) analysis of label information; e) preparation of menu and f) production of conceptual maps. Thus, the work aims to contribute to the development of autonomy and critical sense in the search for a better quality of life from the suggested didactic sequence to discuss and address the theme of indigenous food and nutrition in the school context.